PROFIL GURU MATEMATIKA DI SMP DITINJAU DARI PENGEMBANGAN KEPROFESIAN BERKELANJUTAN - Noviana Dini Rahmawati; Rasiman (Perspektif Ilmu Pendidikan, 2022)
The teaching profession is an effort by the Government to improve the quality of teachers through improving teacher welfare. Teachers who have passed the teacher professional test will be given a professional allowance of one time of basic salary as a form of government efforts to improve teacher welfare. The purpose of this study was to determine the profile of junior high school mathematics teachers in terms of Continuing Professional Development (PKB). This research is a descriptive-qualitative research, namely research conducted using quantitative and qualitative approaches. The research sample was junior high school mathematics teachers and school principals in the city of Semarang. From the results of this study indicate that the profile of junior high school teachers in the city of Semarang, aspects: (1) aspects of self-development, 58% of teachers have good intentions and motivation to participate in these activities, whether organized by schools or other agencies, (2) in the aspect of scientific publications, 32% of teachers carry out scientific publications very well but most of the teachers still having difficulty doing classroom action research and writing scientific articles, and (3) on the aspect of innovative work, 16% of teachers are not interested in making teaching aids, especially IT-based learning media.